Dexamethasone has profound influence on the energy metabolism of porcine blood leukocytes and prevents the LPS-induced glycolytic switch - Ma, Wenjuan; Brenmoehl, Julia; Trakooljul, Nares; Wimmers, Klaus; Murani, Eduard (Frontiers in Immunology, 2025)
In farm animals, little is known about the relationship between energy metabolism of immune cells and their activation state. Moreover, there has recently been evidence that dexamethasone, a powerful glucocorticoid-based drug, can exert its anti-inflammatory effects by interfering with the energy metabolism of immune cells, but the mechanisms are not yet fully understood. To address these knowledge gaps, we explored the connection between the energy metabolism of porcine peripheral blood mononuclear cells (PBMCs) and their response to pro- and anti-inflammatory stimulation with lipopolysaccharide (LPS) and dexamethasone (DEX) in vitro. Interventions in the metabolism of PBMCs with the glycolysis inhibitor 2-deoxy-D-glucose or the HIF-1α inhibitor KC7F2 reduced the LPS-induced TNF-α production, but the mitochondrial ATP synthesis inhibitor oligomycin showed no significant effect. The anti-inflammatory action of DEX was not affected by any of the inhibitors. To investigate the metabolic actions of LPS and DEX in PBMCs, we evaluated glycolysis and mitochondrial respiration following 24 hours stimulation using the Seahorse XFe96 flux analyzer. Our results revealed significantly higher glycolysis in LPS-treated PBMCs, but provided no evidence for a change in mitochondrial respiration. In contrast, DEX reduced LPS-induced glycolysis and, especially when administered alone, significantly lowered mitochondrial respiration. Pretreatment with KC7F2 counteracted the effects of LPS and DEX on glycolysis, and reduced mitochondrial respiration regardless of the inflammatory state of the PBMCs. Gene expression analysis identified the glucose transporter SLC2A3, and the tricarboxylic acid cycle genes IDH1 and SDHB as the main switches for the antagonistic metabolic actions of LPS and DEX, which are closely associated with the inflammatory state of PBMCs.